Phytochemical Screening of Ater Bamboo Shoot Extract (Gigantochloa atter Kurz) with Different Solvents and Their Effect on Antioxidant Activity Using the DPPH Method - Tiara Dhea Febryana; Septian Maulid Wicahco; Vivin Marwiyati Rohmana (International Journal of Health Engineering and Technology, 2025)
An imbalance of free radicals in the body can cause a health condition known as oxidative stress. Oxidative stress is a condition in which free radicals and antioxidants in the body are out of balance. Oxidative stress can be overcome with natural antioxidants. This study aims to determine the antioxidant activity indicated by the IC50 value of the extract of bamboo ater shoots (Gigantochloa atter Kurz) extracted with different solvent polarities. The extraction process was carried out by the maceration method using 96% alcohol solvent, n-Hexane, and ethyl acetate. Each extract was then subjected to phytochemical screening tests, including flavonoids, steroids, alkaloids, tannins, saponins, and terpenoids. Analysis of antioxidant activity in this study was carried out using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results of phytochemical screening showed significant differences among each solvent, where the 96% alcohol solvent showed the most complete phytochemical screening results. Based on the results of the study, it can be concluded that bamboo ater shoots have antioxidant activity, and solvent polarities affect the IC50 value shown. The 96% alcohol extract of bamboo ater shoots has antioxidant activity with an IC50 value of 39.22 µg/mL, the extract of bamboo ater shoots with ethyl acetate solvent is 56.19 µg/mL, and the extract of bamboo ater shoots with n-Hexane solvent is 69.77 µg/mL.